Prof. Dr. Ute Fendler and Cluster fellow Alexandre Vieira on the African diasporic influence on Brazilian culture - Fendler, Ute; Vieira, Alexandre (Cluster Conversations, 2023)
In this episode, Cluster fellow Alexandre Vieira talks with his host Ute Fendler about the African influence on Brazilian music in general and his music in particular. For videos on the mentioned concerts please visit: Concert „Transoceanic Encounters" and Transoceanic Musical Lectures.